(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The article is devoted to the analysis of psychological dimensions of early child development. It is stated that the normative development of a child in the early stages of the genesis of existence is due to the congruence of parental care. This leads to the recognition of the critical destructiveness of predictors of maternal deprivation. Emphasis is placed on the formation of the relationship of interdependence between young children and parents. The article highlights the markers of mental dysontogenesis of preschool children due to the separation of the child from the mother and / or early institutionalization of the child. The main directions of prevention and correction of manifestations of dysontogenesis in the development of a young child in conditions of deficiency of parental care are outlined